2007
DOI: 10.1007/s10544-006-9042-2
|View full text |Cite
|
Sign up to set email alerts
|

Design criteria of neuron/electrode interface. The focused ion beam technology as an analytical method to investigate the effect of electrode surface morphology on neurocompatibility

Abstract: "Neurocompatibility" is a broad definition which comprises aspects of biocompatibility, chemical and physical surface properties, and biostability of an artificial substrate interfaced with a neural tissue. The main issue coming from the analysis of the state of art of neuroprosthesis and neuron/electrode interfaces is the strong influence of electrode surface morphology on neurocompatibility. Enhanced functions of neurons have been observed on nano-structured materials. This paper proposes the use of focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Several works highlighted the possibility to tune this phase by modifying the substrate, adding chemical and physical cues which replicate the natural features of the extracellular matrix (Hubbell 1999). Concerning the surface morphology, it has been demonstrated that cells adhesion is very sensitive to variations in nanometer-scale topography (Raffa et al 2007). An example is given by Washburn (Washburn et al 2004) indicating that nanoroughness values ranging from 0.5 to 13 nm influence the adhesion of MC3T3-E1 osteoblastic cells on substrates coated with poly(L-lactic acid) (PLLA) films.…”
Section: Introductionmentioning
confidence: 99%
“…Several works highlighted the possibility to tune this phase by modifying the substrate, adding chemical and physical cues which replicate the natural features of the extracellular matrix (Hubbell 1999). Concerning the surface morphology, it has been demonstrated that cells adhesion is very sensitive to variations in nanometer-scale topography (Raffa et al 2007). An example is given by Washburn (Washburn et al 2004) indicating that nanoroughness values ranging from 0.5 to 13 nm influence the adhesion of MC3T3-E1 osteoblastic cells on substrates coated with poly(L-lactic acid) (PLLA) films.…”
Section: Introductionmentioning
confidence: 99%
“…The use of high precision machining tools, such as focused ion beams, to modify • surface patterns at nanoscales in ways that in fl uence cell adhesion and other interface characteristics. Scales approximately tens of nanometers to 100 nm, which is the typical scale of cellular interaction in biological systems, seem to generate optimum results (Raffa et al 2007 ;Johansson et al 2006 ) . The design and characterization of nanoelectronic arrays out of functionalized • carbon nanotubes and quantum dot layer-by-layer assemblies that allow for facilitation of neuron growth and development and multi-site communication between 37 2 Applications of Nanotechnology to the Brain and Central Nervous System electronic systems and multi-cellular matrices (Mazzatenta et al 2007 ;Greve et al 2007 ) .…”
Section: Visualizing and Structuring Neural Prosthetic Interfacesmentioning
confidence: 99%
“…In fact, it has been shown that cell adhesion is higher for surface features in the ten’s of nanometer range compared to the hundred’s of nanometer range [104,105] studied the effect of carbon nanofiber coatings on astrocyte proliferation in-vitro . These fibers were either 60 or 200 nm and with either high or low surface energy.…”
Section: Altering the Physical Structure Of The Microelectrodesmentioning
confidence: 99%